Human Development Index In Syria During Period Of Crisis 2011-2018 - محمود يوسف; قابقلي ابتهال; أسعد بسام (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research goal is to present a review of human development index (HDI) issued by the United Nation Development Programme (UNDP) in Syria during the period of war 2011-2018 and to determine the negative effects created by war on the three dimensions of human development index, that are health, education and income. The research uses the descriptive analysis approach to achieve its goals through the theoretical and literatures related to human development, in addition to formal statistics issued by united nation development program reports and official statistics issued by Syrian official organization during the research period. The research shows that the human development as an important issue internationally which is attracts the attention of researchers and academics during last decades in the twentieth century. The research shows also that the human development affected by social circumstances and economic, political, and international conditions, in addition to conflicts and wars over the world, so this is the motivation of research in order to specify and determine the position of human development in Syria and the negative effects on it during research period. The research reaches a results that indicate the period of war in Syria results in many negative effects on human development and these effects will continues for short, medium and long term with different effects among sectors. The economic losses that emerged in Syria during the war are not only substantial or physical losses but reaches to developmental indicators such as accumulative social achievement through a long time and requires a long time to rebuild it.